2003
DOI: 10.4319/lo.2003.48.6.2106
|View full text |Cite
|
Sign up to set email alerts
|

Periphyton density influences organochlorine accumulation in rivers

Abstract: To investigate the influence of eutrophication on organochlorine dynamics in lotic systems, we related polychlorinated biphenyl (PCB) concentrations in brown trout (Salmo trutta) to the periphyton density and total phosphorus concentrations (Tot-P) in 10 Swedish rivers. Tot-P concentrations in the water ranged from 37 Ϯ 4 to 156 Ϯ 51 g L Ϫ1 . Periphyton density in the rivers during the experiment ranged from 6 to 199 mg carbon (C) m Ϫ2 and was not related to the Tot-P concentration. The concentrations of PCB 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 31 publications
0
27
4
Order By: Relevance
“…The retention increases with increasing periphyton density, which constitutes a large immobile surface area with which the POPs can associate, decreasing their downward transport and increasing the probability of uptake in biota. In lakes, an increase in primary producer biomass has been suggested to lower POP concentrations by biomass dilution (Taylor et al 1991), but no such effect was found in these rivers (Berglund 2003). When the effect of periphyton density was removed, the correlation between α and PCB in this study disappeared.…”
Section: Carbon Source and Pcb Concentrationscontrasting
confidence: 63%
See 4 more Smart Citations
“…The retention increases with increasing periphyton density, which constitutes a large immobile surface area with which the POPs can associate, decreasing their downward transport and increasing the probability of uptake in biota. In lakes, an increase in primary producer biomass has been suggested to lower POP concentrations by biomass dilution (Taylor et al 1991), but no such effect was found in these rivers (Berglund 2003). When the effect of periphyton density was removed, the correlation between α and PCB in this study disappeared.…”
Section: Carbon Source and Pcb Concentrationscontrasting
confidence: 63%
“…The relative importance of these factors may vary, but nutrient limitation is of less importance in rivers of this nutrient concentration range (Chételat et al 1999). In the rivers in this study, we found no influence of nutrients, light, or stream velocity on periphyton biomass (Berglund 2003); however, we could not directly estimate the influence of grazing pressure in this study, as our sampling of invertebrates was not quantitative. POP concentrations in river biota have been shown to increase with increasing periphyton density (Berglund 2003).…”
Section: Carbon Source and Pcb Concentrationscontrasting
confidence: 58%
See 3 more Smart Citations